2016
DOI: 10.1101/070730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic correlations among psychiatric and immune-related phenotypes based on genome-wide association data

Abstract: Individuals with psychiatric disorders have elevated rates of autoimmune comorbidity and altered immune signaling. It is unclear whether these altered immunological states have a shared genetic basis with those psychiatric disorders. The present study sought to use existing summary-level data from previous genome-wide association studies (GWASs) to determine if commonly varying single nucleotide polymorphisms (SNPs) are shared between psychiatric and immune-related phenotypes. We estimated heritability and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 139 publications
4
54
0
Order By: Relevance
“…Recent research suggests a genetic overlap between several autoimmune diseases and psychiatric disorders; however, the only study that has included EDs revealed no significant genetic associations between AN and autoimmune diseases or traits (Tylee et al., ). The increased risk for EDs after type 1 diabetes could be metabolically mediated through a dysregulation of insulin homeostasis, administration of mandatory external insulin, and insulin misuse (Bryden et al., ; Colton et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests a genetic overlap between several autoimmune diseases and psychiatric disorders; however, the only study that has included EDs revealed no significant genetic associations between AN and autoimmune diseases or traits (Tylee et al., ). The increased risk for EDs after type 1 diabetes could be metabolically mediated through a dysregulation of insulin homeostasis, administration of mandatory external insulin, and insulin misuse (Bryden et al., ; Colton et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As the size of genomic investigations of both EDs and autoimmune diseases increases, we will be well positioned to further explore the extent to which shared genetic factors influence risk for both classes of illness. However, first evidence does not support a genetic overlap between autoimmune traits and AN estimated by genetic correlations derived from molecular genetic methods (Tylee et al., ). The finding, however, requires replication and extension to other ED types.…”
Section: Discussionmentioning
confidence: 99%
“…Another common denominator for various mental disorders is aberrations of the immune system; increased levels of pro-inflammatory cytokines, such as IL-1beta, IL-6 and TNF have been reported in patients with schizophrenia, bipolar disorder, and depression 58 , and pathway analysis by the Psychiatric Genomics Consortium identified histone modifications, synaptic density, and immune and neuronal signaling pathways in common for schizophrenia, depression and bipolar disorder 59 . Further, genetic correlations between immune-related disorders and a number of psychiatric conditions have been reported in a recent study combining data from several GWAS 60 .…”
Section: Neuroimmunology and Psychiatric Disordersmentioning
confidence: 88%
“…Like ASD, there is a substantial body of data indicating that genetic factors, immune dysregulation and neuroinflammation are all involved in at least a subset of cases. Whole genome analyses have identified 108 conservatively defined loci that meet genome-wide significance 49,50 . Many of these genes are highly expressed in the brain, as well as in immune function, including the HLA region on chromosome 6 51 .…”
Section: Genetic Riskmentioning
confidence: 99%
“…For example, a GWAS study (1,285 TS subjects and 4,964 controls) implicated several pathways related to specific astrocytic, oligodendrocytic and microglial activity, as well as to synaptic function 62 . More recently, Tylee et al 50 re-examined the available GWAS data from individuals with TS, OCD, and ADHD and found significant genetic correlations between psychiatric and immune-related phenotypes based on genome-wide association data. These findings are also consistent with the findings of two large scale, populationbased, epidemiological studies from Denmark and Sweden, which have documented that some individuals with OCD, TS, and ADHD have an increased risk for developing an autoimmune disorder [63][64][65] .…”
Section: Genetic Riskmentioning
confidence: 99%